The structural, electronic properties, pressure response and decomposition mechanism of bispentazole (N10) with first principles calculations - Han Qin; Fei Li; Ying-Xu Zhou; Hui-Dong Li; Fu-Sheng Liu; Zheng-Tang Liu; Qi-Jun Liu (Results in Physics, 2023)
Bispentazole (N10) is one of the recently-found full-nitrogen energetic materials, which have remarkable performance in the pursuit of higher energy and greener explosive. Therefore, the structural, electronic properties, pressure response, and decomposition mechanism of four types of N10, namely P21-N10, I-N10, V-N10, and P-N10, are investigated using first-principles calculations. Our results show that all the structures are thermodynamic stability, and P21-N10 and P-N10 are dynamical stability. All N10 structures belong to insulators with indirect band gaps. The results show that the N-N bond on the five-membered cyclic ring, which is on the opposite side of the N-N bond connected to the two five-membered cyclic rings, is relatively weak. From the decomposition pathway of the N10 molecule, it can be observed that the product N2 is gradually separated from two cyclic N5 rings in the molecule. The result demonstrated that the N-N bond in full-nitrogen materials can release energy by breaking of N-N bond to form the stable N2. The calculated three reaction energy barriers means that the decomposition temperature of N10 is lower than that of N8 and N6. Finally, the released energy as 168.0 kcal/mol indicates that the N10 molecule can release a lot of energy when it decomposes.